Anthropometric characteristics and somatotype of young Greek rowers - Kaloupsis, S.; Bogdanis, G. C.; Dimakopoulou, E.; Maridaki, M. (Biology of Sport, 2008)
This study examined selected anthropometric characteristics of young rowers and compared them with those of senior national level athletes and untrained children, in order to establish a rowing specific anthropometric profile for young athletes. Anthropometric characteristics were measured in 509 club-level rowers aged 11-16 years and 29 male senior national level rowers. Club-level athletes were categorized in 6 age groups (11-16 y), while the senior national level rowers were divided into heavyweight (H-W) and lightweight (L-W). Rowers aged 15 and 16 y had similar height, body weight, arm length and leg length, but lower lean body mass (5 to 8.3 Kg less) compared with senior L-W rowers. Comparison of the young rowers with a reference group of untrained Greek children by means of percentiles (P) revealed that rowers in all age groups were heavier (P63 to P75), taller (P82 to P90) but had a lower body mass index than the mean values (P50) of the reference group after the age of 14 (P48 to P43). Skinfold thicknesses and body fat decreased from the 11 y through to the 16 y group (from 22.9% to 17.8%), and were lower in the two senior groups (9.6% for the L-W and 12.3% for the H-W). Endomorphy ratings decreased with age from 11 to 14 y, but there was no difference between the 14 to 16 y old groups. Mesomorphy was similar across all groups examined and ectomorphy did not show large fluctuations from the 13 y old group onwards. Somatotype of the 15 y old group was 2.4-4.4-3.4 (endo-meso-ectomorphy) and was identical to that of the 16 y group and the lightweight senior rowers. The results of this study showed that the club level rowers aged 15 and 16 yrs have similar body structure but different body composition compared with the senior L-W rowers. Anthropometric characteristics can be used as a criterion for selection of rowers by the coaches from an early age.